Potency testing of cell and gene therapy products - Salmikangas, Paula; Carlsson, Björn; Klumb, Christophe; Reimer, Tatiana; Thirstrup, Steffen (Frontiers in Medicine, 2023)
Potency is one of the critical quality attributes of biological medicinal products, defining their biological activity. Potency testing is expected to reflect the Mechanism of Action (MoA) of the medicinal product and ideally the results should correlate with the clinical response. Multiple assay formats may be used, both in vitro assays and in vivo models, however, for timely release of the products for clinical studies or for commercial use, quantitative, validated in vitro assays are necessary. Robust potency assays are fundamental also for comparability studies, process validation and for stability testing. Cell and Gene Therapy Products (CGTs, also called Advanced Therapy Medicinal Products, ATMPs) are part of biological medicines, having nucleic acids, viral vectors, viable cells and tissues as starting material. For such complex products potency testing is often challenging and may require a combination of methods to address multiple functional mechanisms of the product. For cells, viability and cell phenotype are important attributes but alone will not be sufficient to address potency. Furthermore, if the cells are transduced with a viral vector, potency probably is related to the expression of the transgene but will also be dependent on the target cells and transduction efficiency/copy number of the transgene in the cells. Genome Editing (GE) together with other cell manipulations can result into multiple changes in the characteristics and activity of the cells, which should be all somehow captured by the potency testing. Non-clinical studies/models may provide valuable support for potency testing, especially for comparability testing. However, sometimes lack of suitable potency data may lead to situations where bridging clinical efficacy data are required to solve the problems of the potency testing, for example where comparability of different clinical batches is unclear. In this article the challenges of potency testing are discussed together with examples of assays used for different CGTs/ATMPs and the available guidance addressing differences between the European Union and the United States.